Study on defense efficiency in senior volleyball teams - Cojocaru, A.-M.; Cojocaru, M. (Science, Movement & Health, 2021)
Objective. The purpose of this study was to study a performance model in volleyball, at the level of seniors in Romania, in defense actions and especially the relationship between blocking and taking over the attack, so as to achieve an increase in the efficiency of the attack on break point. Methods. All games were recorded and analyzed using Data Volley software (Data Volley 2007). Data was collected and exported from Data Volley 2007 software using program-specific spreadsheets and adapted to game analysis. Each spreadsheet contained the performance of the players and teams during the sets. Results. The study highlights the technical-tactical performance model of the blocking and defense actions, during the game, related to the attack made by the opponent, on several tempos. Depending on the importance of the games, there is also a significant increase in defense, especially in the attack made during time 3, and in terms of performance, there was an increase in the efficiency of defense in the attack made with 2 or three players blocking. Conclusions. This study is the first step in developing a technical-tactical performance model of the relationship between blocking and taking over the attack. The higher the efficiency of the defense in attack, the higher the points of attack after defense.